2021
DOI: 10.1097/ppo.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy in Oligomestatic/Oligoprogressive Sarcoma

Abstract: Background: Metastatic soft tissue sarcoma (STS) patients may benefit from local ablative treatments due to modest efficacy of systemic chemotherapy. However, use of stereotactic body radiotherapy (SBRT) is controversial because of presumed radioresistance of STS.Methods: Patients treated with SBRT for oligometastatic and oligoprogressive metastatic STS were retrospectively reviewed to assess results in terms of local control (LC), disease-free survival (DFS), and overall survival (OS). Incidence and grade of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…On the contrary, some studies, which analyzed both intra- and extra-thoracic metastatic lesions, showed a statistically significant dose-response relationship. Greto et al [ 29 ] analyzed 77 metastatic lesions from 40 patients treated by SBRT. 60% of the lesions were pulmonary metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, some studies, which analyzed both intra- and extra-thoracic metastatic lesions, showed a statistically significant dose-response relationship. Greto et al [ 29 ] analyzed 77 metastatic lesions from 40 patients treated by SBRT. 60% of the lesions were pulmonary metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of surgery in controlling lung metastases and improving survival has been shown in STS [23,24]. The role of SBRT for oligometastatic STS appears to be both safe and effective [25,26]. Hypofractionated radiation for palliation may allow for improvement of patient quality of life and compared to conventionally fractioned approaches affords decreased treatment time and possibly an increased durability of palliative response.…”
Section: Future Role For Mri In Radiation For Stsmentioning
confidence: 99%
“…In the current issue of the Cancer Journal , Greto et al 2 report their experience using lung stereotactic body radiation therapy (SBRT) for oligometastatic sarcoma. Their study shows promising rates of local control (2-year local control, 67%) and survival (2-year overall survival, 40%).…”
mentioning
confidence: 99%
“…The article by Greto et al 2 adds to the growing body of evidence supporting the use of lung SBRT for sarcoma metastases. Comparison studies of the various ablative modalities and surgery would be beneficial but are unlikely to happen, given the rarity of sarcoma and challenges in enrolling patients on these types of clinical trials.…”
mentioning
confidence: 99%